An autonomous moving heuristic for mobile sink based on feasible sojourn regions to maximise network lifetime in wireless sensor networks. (1st January 2014) - Anne, Regis W.; Rajsingh, Elijah Blessing
Most of the research in wireless sensor networks (WSN) concerns the maximisation of network lifetime by avoiding the formation of energy hole in the sink neighbourhood. The energy hole formation incurs heavy casualties on network lifetime which results in early failure of the entire network. This is because of the premature death of sensors in the sink's immediate locality which can be postponed by exploiting sink mobility. In this work, first we have given an analytical formulation of the problem, a centralised approach. Second, a distributed and localised LED (load, energy and density) heuristic is proposed where an energy-wise region for the mobile sink to sojourn is decided based on a collective formula derived from load, energy and density profiles of a sensor and its neighbours. Extensive simulations in MATLAB reveals that the proposed method effectively increases the network lifetime by 300% over other conventional strategies thus creating uniform energy distribution and load balance among the nodes in the network. Finally, extensions to the heuristic are provided to further enhance network lifetime.